P.006 Etiologic diagnoses of rapidly progressive dementia in a prospective multicenter cohort. (June 2022) - Day, GS; Tipton, PW; Lazar, E; Martens, YA; Dunham, S; Geschwind, MD; Bu, G; Morris, JC; Graff-Radford, NR
Abstract : Background: Accurate etiologic diagnoses are needed in patients with rapidly progressive dementia (RPD) to ensure access to symptomatic and disease-modifying therapies when available. Methods: Patients with RPD were prospectively enrolled and evaluated at Washington University (Saint Louis, MO; 2016-2019) and Mayo Clinic (Jacksonville, FL; 2020-2021). Etiologic diagnoses were independently assigned by two dementia specialists integrating clinical features and the results of diagnostic tests; disagreements were resolved via blinded review by a third specialist. Results: 160 RPD patients were enrolled and followed. Average age-at-symptom onset was 60.0±15.9 years; 50% were female. Inter-rater reliability (91% agreement; Cohen's κ=0.88, p<0.001) and clinicopathologic correlation were excellent (100% agreement in 24 patients with neuropathologic data). Autoimmune encephalitis was the leading cause of RPD (39%), followed by Alzheimer disease and related dementias (29%), Creutzfeldt-Jakob disease (15%), and other causes (15%). Patients with potentially treatable causes of RPD were younger (54.5±18.2 than those with neurodegenerative causes (67.3±9.5; p<0.001), and more likely to present with altered levels of consciousness, seizures, or CSF pleocytosis (p<0.05). Conclusions: Etiologic diagnoses can be reliably established in RPD patients using available clinical data. The prevalence of autoimmune encephalitis in this series justifies routine screening for potentially treatment-responsive causes of RPD, particularly in younger patients.